Vertical and Horizontal Plastic Litter Distribution in a Bend of a Tidal River - Blondel, Elise; Buschman, Frans A. (Frontiers in Environmental Science, 2022)
Plastic litter transported in rivers may enter the marine environment. Due to the durability of plastic, the residence times in the aquatic environment are decades to millennia. Plastic litter items come in a wide variety. The density of the item and the flow velocity largely determine the vertical distribution of the plastic litter, although the litter shape and wind can also play a role in a river. The estimates of the plastic transport in a river are usually based on observations of visible litter items in the near-surface layer alone. Only a very limited number of studies have observed the vertical distribution in rivers or estuaries. We have carried out 28 sampling surveys in a river bend located in the lower part of the Rhine-Meuse delta that is under the influence of tides. To observe the vertical distribution, we sampled with three nets simultaneously up to 5m water depth, at both sides of a river bend. We observed that by mass and by number the plastic mass concentration in the middle net was substantially lower than in the lower and upper nets. In total, more plastic litter was present in the lower two nets than in the surface net. A higher plastic concentration was found at the downwind side of the channel than at the upwind side of the fairway. It was found that the plastic litter mass concentrations were of the same order of magnitude and somewhat higher during ebb than during flood tide. The litter size that contributed most to the mass concentration were items in between 25-500 mm, which were mostly soft plastics (i.e. foils). In the lower net relatively more and somewhat smaller hard plastic items were found. It was observed that these plastic items were sometimes entangled in organic matter. The plastic flux lower in the water column may follow the transport of organic matter like aquatic plants.